GAMBARAN KONTINEN PADA LANSIA DI DESA TAMBAR UTARA - Ninuk, Devin Prihar (Universitas Pesantren Tinggi Darul Ulum, 2018)
The continent on elderly is the ability of elderly to control urinate / defecate completely by self. Elderly experience the inability to control urinate / defecate Due to physical deterioration. General Purpose to Know the Overview of continent on Elderly in Tambar Utara Village. This research was conducted using descriptive research with survey approach. The type of this research is descriptive with survey approach. Descriptive method is intended to describe the important events that occur on the client. In this study using probability Sampling with Simple Random Sampling type of sampling technique by selecting each element and randomly selected. The sample consisted of 90 respondents selected at random.The results of this research show that continent at tambar utara village with average of elderly at tambar utara village be able in Activity Of Daily Living (ADL).Keywords: Activity Of Daily Living (ADL), Elderly